1993
DOI: 10.1126/science.8456299
|View full text |Cite
|
Sign up to set email alerts
|

Polar Location of the Chemoreceptor Complex in the Escherichia coli Cell

Abstract: The eukaryotic cell exhibits compartmentalization of functions to various membrane-bound organelles and to specific domains within each membrane. The spatial distribution of the membrane chemoreceptors and associated cytoplasmic chemotaxis proteins in Escherichia coli were examined as a prototypic functional aggregate in bacterial cells. Bacterial chemotaxis involves a phospho-relay system brought about by ligand association with a membrane receptor, culminating in a switch in the direction of flagellar rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
693
1
6

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 700 publications
(732 citation statements)
references
References 39 publications
32
693
1
6
Order By: Relevance
“…Membrane-associated patches of ternary signaling complexes, containing chemoreceptors, the CheA histidine kinase and the coupling protein, CheW, were first detected by immunogold labeling of fixed, sectioned cells [18], later by imaging of fluorescently tagged chemotaxis proteins in living cells [8,19] and most recently by electron tomography of intact cells in vitreous ice [20]. All three methods detect no more than a few patches per cell, with most (~80%) located at a cell pole, although not at any particular position along the polar membrane.…”
Section: Patches Provide the Physical Organization In Which Functionamentioning
confidence: 99%
“…Membrane-associated patches of ternary signaling complexes, containing chemoreceptors, the CheA histidine kinase and the coupling protein, CheW, were first detected by immunogold labeling of fixed, sectioned cells [18], later by imaging of fluorescently tagged chemotaxis proteins in living cells [8,19] and most recently by electron tomography of intact cells in vitreous ice [20]. All three methods detect no more than a few patches per cell, with most (~80%) located at a cell pole, although not at any particular position along the polar membrane.…”
Section: Patches Provide the Physical Organization In Which Functionamentioning
confidence: 99%
“…Data from microscopy, covalent cross-linking, and x-ray crystallography experiments have revealed that cell surface receptors from many structural classes assemble into multi-receptor complexes; these include some heptahelical G-protein coupled receptors (GPCRs), [36][37][38] methyl-accepting chemotaxis proteins (MCPs), [39] gated ion channels, [40] receptor protein tyrosine kinases (RPTKs), [41,42] and multichain immune recognition receptors (MIRRs). [22,33,35,[43][44][45] The size of these ensembles varies: Some complexes are composed of two receptors while others contain thousands.…”
Section: Signaling Complexesmentioning
confidence: 99%
“…[22,33,35,[43][44][45] The size of these ensembles varies: Some complexes are composed of two receptors while others contain thousands. Some receptors, [46][47][48] including the ryanodine receptor [40] and MCPs, [39] are so highly concentrated that they dominate certain subcellular regions. Unfortunately, little is known about the structures of these assemblies, where they are localized within the cells, and how their localization influences signaling.…”
Section: Signaling Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have therefore applied newly developed immunofluorescence microscopic methods (Maddock & Shapiro 1993;Harry et al 1995;Pogliano et al 1995) to study the accumulation and cellular distribution of j F and its regulators during sporulation. Using affinity-purified antisera we have been able to visualize j F , SpoIIAB and the phosphorylated and non-phosphorylated forms of SpoIIAA.…”
Section: Introductionmentioning
confidence: 99%